EKSPRESI SPERMATOGENESIS TIKUS PUTIH SETELAH INDUKSI DENGAN PROTEIN INSULIN LIKE GROWTH FACTOR–I COMPLEX PLASMA SEMINALIS KAMBING - Suherni Susilowati (The East Java Biological Society, 2008)
The objective of this research was to analyzed the expression of spermatogenesis on white rat after inducted by Insulin Like Growth Factor – I (IGF-I) Complex protein from goat seminal plasm. This research consisted of two phase. The fi rst phase was explorative laboratory experiment concerned with identification, isolation and spesifi cation IGF-I Complex by using gel Native Polyacrylamid gel electroforesis, electroelution and Western Blot. Result of gel Native PAGE indicated that of goat seminal plasm with Comassie Blue Stain consisted of seven bands. Result of Western Blot indicated that molecule of IGF-I Complex of goat seminal plasm to bound specific with anti IGF-I Complex at protein ribbon. The second phase concerned with expretion of spermatogenesis on white rat after induction with isolat of IGF-I Complex protein. Result of the expression spermatogenesis on white rat after induction IGF-I Complex to show the signifi cant different between three groups (p < 0.05). From result above can be concluded that IGF-I Complex protein can increase the total of spermatocyte I and spermatocyte II.